Generation and Storage of Renewable Energy: Rising Parity of Emerging Economies - Gingerich, Elizabeth (International Journal of Energy Economics and Policy, 2018)
While trade liberalization has advanced considerably since post-WWII, emerging economies have disproportionately borne the brunt of trade inequities. However, with a growing consensus that the world must quickly and collectively combat the threat of climate change, certain unexpected phenomena in trade relations are occurring. More developed economies are experiencing a wave of nationalism and self-imposed isolation, jeopardizing the very existence of regional trading blocs and agreements and weakening the World Trade Organization’s (WTO) centralist position in market liberalization (Donnan, 2016-A). However, as technological innovations transform clean energy into a thriving export-import item, emerging economies are discovering a new place in the world market – and buttressing the efficacy of the WTO in the process. Fossil fuel gluts and shortages, catastrophic oil spills, poisonous methane leaks, and fracking-based earthquakes have created an existential threat. But clean energy development, storage, and distribution have experienced significant breakthroughs. With more affordable materials, subsidized infrastructure networking, advantageous topographies and coveted mineral deposits, historically colonized least developed countries (LDCs) may be on track to become formidable trading partners, generating revenue for their own nation-states while assuming greater leadership parity in the universal quest to decarbonize the global economy. And with the widespread acknowledgement of planetary degradation and species extinction, 195 countries – representing developed, developing, and least developed economies alike – successfully negotiated the 2015 Paris Agreement to address greenhouse gas (GHG) emissions mitigation and adaptation (UNFCCC, 2015). Using endemic resources to generate clean energy will not only help participating countries attain their Agreement pledges, but emerging economies may now have a prime opportunity to actively participate in the global marketplace. Keywords: Renewable Energy, World Trade Organization, Greenhouse Gases, Emerging Economies, Mitigation and Adaptation, Regional Trade Agreements JEL Classifications: F13, Q2